Enhancing Vocational Students’ Cognitive Skills in Computer Networking Through Augmented Reality - Hidayat, Arif; Sutopo, Yeri; Qudus, Nur (Universitas Negeri Semarang, 2024)
This study aimed to develop and evaluate Augmented Reality (AR)-based learning media to enhance students’ cognitive abilities at State Vocational High School (SMK Negeri) 2 Pati, particularly in the subject of Computer Networking and the Internet. The research was motivated by low student achievement in meeting the Minimum Mastery Criteria (KKTP), which was primarily attributed to the continued reliance on traditional teaching methods and low student motivation. A research and development (R&D) approach was employed using the ADDIE model. The resulting AR media is an Android application that integrates text, audio, images, animations, interactive 3D objects, and simulations, and is in accordance with the Merdeka Curriculum. Expert evaluations showed a very high level of feasibility, with ratings of 94% from a subject matter expert and 91% from a media expert. These results were further supported by Aiken’s V index, which indicated very high validity for the material (0.921) and high validity for the media (0.881). A practicality test was conducted, revealing a high level of effectiveness, with a 94% approval rating from both teachers and students. Moreover, a pretest–posttest control group design demonstrated significant progress in learning outcomes. The experimental group achieved an average post-test score of 83.75, significantly higher than the control group’s 73.60. Based on the N-Gain test, the experimental group achieved an average gain of 65.52% (moderately effective), whereas the control group achieved only 38.75% (ineffective). This study contributes to the theories of learning transfer, connectivism, and heutagogy, and offers practical implications for vocational education in adopting innovative technologies.